TEACHER’S ROLE IN AI-SUPPORTED ENGLISH LANGUAGE CLASSROOMS - Kayimova Nargiza Rahmatqul qizi (Bright Mind Publishing, 2025)
This article examines the evolving role of teachers in AI-supported English language classrooms. As artificial intelligence technologies such as intelligent tutoring systems, speech recognition tools, automated assessment, and generative language models become increasingly integrated into English language teaching, the professional responsibilities of teachers are undergoing significant transformation. The study adopts a qualitative, literature-based approach to analyze how teachers function as pedagogical mediators, instructional designers, facilitators of learner autonomy, and ethical decision-makers in AI-enhanced learning environments. The findings suggest that while AI can effectively support personalization, practice, and formative assessment, it cannot replace the human dimensions of language teaching, including intercultural mediation, emotional support, and communicative authenticity. The article concludes that the successful implementation of AI in English language education depends on teachers’ digital pedagogy, critical awareness, and informed integration of technology in line with communicative and learner-centered principles.
Keywords: Artificial intelligence, English language teaching, teacher role, AI-supported classrooms, digital pedagogy.